Multi-physics Coupling within Chalk River Unidentified Deposit on Pressurized Water Reactor Fuel Rod - GAO Quanyi1, CONG Tenglong1, TIAN Hongkang1, LIU Maolong2, GU Hanyang1 (Yuanzineng kexue jishu, 2025)
The formation of Chalk River unidentified deposit (CRUD) on the surfaces of fuel rods within pressurized water reactor (PWR) causes significant operational challenges. This study focuses on the characteristics of heat and mass transfer processes within CRUD, which is crucial for improving reactor safety and efficiency. The accumulation of boron in CRUD influences coolant saturation temperature, affecting thermal properties and increasing the risk of CRUD-induced power shift (CIPS), which can lead to substantial economic losses. To address these issues, a two-dimensional CRUD chemistry model (CCM) based on a wick boiling structure was developed. This model integrated multiple physical processes, including boiling heat transfer, capillary flow, mass transport, chemical reactions, and radiolytic decomposition, to accurately predict temperature, flow velocity, and concentration distributions within CRUD. The heat transfer model used wick boiling model to calculate temperature distributions within CRUD, incorporating evaporative heat transfer on the surfaces of steam chimney. The heat transfer model obtained saturation temperature from the solute transport model and provided evaporative water flux to the fluid model. Using Darcy’s law, the fluid model calculated pressure distributions and velocity profiles within CRUD, which facilitated convective mass transfer to the solute transport model. The transport model simulated the transport of species by using diffusion and convection. The sources and sinks of mass within this model were governed by the chemical reaction model and radiolysis model. Research reveals that considering volatilization of boric acid results in predictions of cladding surface temperature that is closer to those observed in WALT experiment. The saturation temperature within CRUD correlates with boron concentration, peaking at 619.32 K as soluble boron accumulates on the cladding surface. Boron in CRUD exists in three forms: soluble boron, precipitated boron and adsorbed boron, with soluble boron predominating at 98.527 5%. Additionally, the pH increase at the bottom of the CRUD layer significantly influences LiBO2 precipitation, which is pH-dependent at specific temperatures. The study also analyzed the impact of CRUD geometric parameters such as thickness, porosity, chimney density, and chimney radius on boron accumulation and the heat transfer performance of fuel rods. These findings provide a robust framework for understanding the complex interactions within CRUD layer on fuel rods in PWRs, offering valuable insights into CRUD formation mechanisms and their impact on reactor operation.